2021
DOI: 10.1007/s00394-021-02521-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving insulin sensitivity, liver steatosis and fibrosis in type 2 diabetes by a food-based digital education-assisted lifestyle intervention program: a feasibility study

Abstract: Purpose Recent trials demonstrated remission of type 2 diabetes and non-alcoholic fatty liver disease (NAFLD) following formula diet-induced weight loss. To improve the outreach for populations in need, many mobile health apps targeting weight loss have been developed with limited scientific evaluation of these apps. The present feasibility study investigated the effects of a novel approach incorporating a regular ‘whole food-based’ low-calorie diet combined with app-based digital education and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The 42 studies were published between January 1, 2010, and March 31, 2022, with as many as 28 (67%) published within the past 6 years [ 29 - 56 ]. We found that, in 2021, nearly twice as many articles were published on the topic as in each of the previous 4 years ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 42 studies were published between January 1, 2010, and March 31, 2022, with as many as 28 (67%) published within the past 6 years [ 29 - 56 ]. We found that, in 2021, nearly twice as many articles were published on the topic as in each of the previous 4 years ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Information on complex telehealth interventions used for diabetes self-management and monitoring with health professional involvement was obtained for 18 countries. Of the 42 studies, 11 (26%) were conducted in the United States [ 30 , 31 , 39 , 48 - 51 , 57 - 59 ]; 5 (12%) in South Korea [ 37 , 41 , 44 , 60 , 61 ]; 4 (10%) in Singapore [ 29 , 43 , 46 , 55 ]; 4 (10%) in Norway [ 32 , 62 , 63 ]; 3 (7%) in the United Kingdom [ 33 , 35 , 38 ]; 3 (7%) in Germany [ 40 , 45 , 56 ]; 2 (5%) in China [ 47 , 64 ]; and 1 (2%) each in Australia [ 54 ], South Africa [ 65 ], Spain [ 66 ], Iran [ 52 ], Italy [ 67 ], Japan [ 42 ], Lebanon [ 34 ], Slovenia [ 36 ], Switzerland, and Taiwan [ 68 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, digital education will likely assume increasing importance in the management of NAFLD. In a recently conducted clinical trial, 12 weeks of diet and exercise supported by digital education reduced body weight by ~ 9% and resolved NAFLD in 30% of participants with NAFLD and T2DM [46]. A major limitation of all lifestyle modification programs is non-compliance and the inability to sustain weight loss beyond the prescribed program.…”
Section: Lifestyle Modificationmentioning
confidence: 99%